2020
DOI: 10.3389/fped.2020.00355
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for the Discrimination of Acute Kawasaki Disease From Infections in Childhood

Abstract: Background: Kawasaki disease (KD) is a vasculitis of early childhood mimicking several infectious diseases. Differentiation between KD and infectious diseases is essential as KD's most important complication-the development of coronary artery aneurysms (CAA)-can be largely avoided by timely treatment with intravenous immunoglobulins (IVIG). Currently, KD diagnosis is only based on clinical criteria. The aim of this study was to evaluate whether routine C-reactive protein (CRP) and additional inflammatory param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Although there are shared features between the response to KD and both bacterial and viral infections, the distinct pathways enriched in each disease group demonstrate the variation in the molecular host response; the distinctiveness of the responses is also supported by the ability of RNA and protein signatures to discriminate KD from bacterial and viral infections [ 18 , 19 , 35 ]. These differences between the response during KD and the responses to bacterial and viral infections suggest that KD may be triggered by a novel process not typical of either common bacterial or viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are shared features between the response to KD and both bacterial and viral infections, the distinct pathways enriched in each disease group demonstrate the variation in the molecular host response; the distinctiveness of the responses is also supported by the ability of RNA and protein signatures to discriminate KD from bacterial and viral infections [ 18 , 19 , 35 ]. These differences between the response during KD and the responses to bacterial and viral infections suggest that KD may be triggered by a novel process not typical of either common bacterial or viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Neutropenic episodes were categorised by their course: samples taken in the absence of fever, during FN (mild FN), and during infection‐related complications requiring intensive care unit (ICU) treatment (complicated FN). We assessed the concentration of C‐reactive protein (CRP), 9,10 interleukin 8 (IL‐8), 9 human neutrophil elastase (HNE), 10 myeloid‐related protein‐8/14 (MRP8/14) 10 and nucleosomes 11 to predict infection, ICU admission and bone marrow recovery in patients with AML after high‐dose induction chemotherapy. During neutropenia, all patients received prophylaxis with penicillin, ciprofloxacin and fluconazole.…”
Section: Figurementioning
confidence: 99%
“…The theories about hygiene or the under-challenged immune system due to low exposure to environmental or infectious agents, have been suggested to contribute to a pathological response to a pathogen (69), which may be relevant to triggering KD in genetically susceptible children. Several studies have shown an increase of allergies in KD patients compared to the general population, which may support a link between hygiene and environmental conditions involved in the slow but progressive rise in KD incidence worldwide which can be neither caused by improved recognition and diagnostic skills of doctors nor by current laboratory tests for KD since these are not yet applicable (70)(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%